Environmental, economic and engineering performances of aqueous carbonated steel slag powders as alternative material in cement pastes: Influence of particle size - Li, X.; Mehdizadeh, H.; Ling, T. C.
The low reactivity and volume expansion issue of steel slag limits its application as alternative to cement. Studies demonstrated that aqueous carbonation (AC)can enhance the cementitious properties of finely sized steel slag as a cementitious supplementary material (SCM). However, the impact of particle size on the CO2 uptake capacity and its association of performance of carbonated steel slag remains unexplored. This study aims to optimize the grinding levels by examining the fineness of the steel slag used as SCM to reduce the high-energy consumption while maintaining the CO2 sequestration and properties of SCM. The results show that reducing the size of steel slag is favorable for CO2 sequestration (particle size 22.4-112.6 ?m corresponds to sequestration of ?88.5-37.9 kg CO2/t steel slag)and improve the leaching of Mg ions for mineralization. The life cycle assessment shows that the global warming potential of AC of steel slag is ?96.2-24.9 kg CO2-eq/t steel slag, which can offset the carbon emissions due to further grinding. The 28-day compressive strength of the cement pastes blended with finer carbonated steel slag was also relatively higher due to the formation of mono-carboaluminates and stabilization of ettringite in facilitating the bond strength between the carbonated steel slag particle and the cement paste matrix. According to 3E (engineering, environmental and economic)triangle model, 22.4 ?m steel slag powder showed the best comprehensive performance, including an increased revenue of 40.8 CNY/ton steel slag.
Keywords: AQUEOUS CARBONATION; CEMENT PASTE; COMPREHENSIVE PERFORMANCE ASSESSMENT; PARTICLE SIZE EFFECT; STEEL SLAG